Biological nitrification inhibition activity in a soil-grown biparental population of the forage grass, Brachiaria humidicola - Nuñez, Jonathan; Arévalo, Ashly; Karwat, Hannes; Egenolf, Konrad; Miles, John W.; Chirinda, Ngonidzashe; Cadisch, Georg; Rasche, Frank; Rao, Idupulapati M.; Subbarao, Guntur; Arango, Jacobo (Springer, 2018)
Aim: Utilization of biological nitrification inhibition (BNI) strategy can reduce nitrogen losses in agricultural systems. This study is aimed at characterizing BNI activity in a plant-soil system using a biparental hybrid population of Brachiaria humidicola (Bh), a forage grass with high BNI potential but of low nutritional quality. Methods: Soil nitrification rates and BNI potential in root-tissue were analyzed in a hybrid population (117), obtained from two contrasting Bh parents, namely CIAT 26146 and CIAT 16888, with low and high BNI activity, respectively. Observed BNI activity was validated by measuring archaeal (AOA) and bacterial (AOB) nitrifier abundance in the rhizosphere soil of parents and contrasting hybrids. Comparisons of the BNI potential of four forage grasses were conducted to evaluate the feasibility of using nitrification rates to measure BNI activity under field and pot grown conditions. Results: High BNI activity was the phenotype most commonly observed in the hybrid population (72%). BNI activity showed a similar tendency for genotypes grown in pots and in the field. A reduction in AOA abundance was found for contrasting hybrids with low nitrification rates and high BNI potential. Conclusion: Bh hybrids with high levels of BNI activity were identified. Our results demonstrate that the microcosm incubation and the in vitro bioassay may be used as complementary methods for effectively assessing BNI activity. The full expression of BNI potential of Bh genotypes grown in the soil (i.e. low nitrification rates) requires up to one year to develop, after planting.